O combate ao trabalho infantil no Brasil: avanços e retrocessos - Matos, Leonardo Raphael Carvalho de (2015)
Relevant subject within the law relations is the child labor and its relationship with the human rights protection. From a post-positivist view and the private publicity phenomenon, human rights nowadays enjoy legislative protection, sovereignty of their standards and a special attention from the Law. The interests between individuals suffer a direct reflection of the constitutional and international standards, as they are part of a social whole, diffuse rights holders. Another aspect to be analyzed is the one that concerns to legislative mutation with prominence to its interpretation, at the time the legal norm becomes a compound of normative determinations of heteronomous and ambiguous character, assuming, then, a new legal nature from a modern systematic hermeneutics, mainly to approved international standards that have effect in the Brazilian legal system. Will be analyzed, even for the hypothetical-deductive method, the influence of human rights and constitutional principles in labor Law as legal science, considering the fight against child labor and the work of the Ministry of Labor, analyzing the legal literature. In the next moment, through the inductive method, will be discussed the child labor and the relevant legislation. Then will be cited the national programs to fight child labor, implemented by the National Coordination of preventive Combating labor exploitation of children and teenagers, as a Ministry of Labor organ and their repressive actions. In the final moment, through the inductive method, official data will be analyzed to indicate the presence of child labor in Brazil, through the verification of published reports by the Ministry of Labor and the Brazilian Institute of Geography and Statistics, in a final counterpoint between the obtained and the desired results.